Influence of alkali treatment on the mechanical properties of new cane fibre/polyester composites. (August 2015) - Chikouche, M Dj Ladghem; Merrouche, A; Azizi, A; Rokbi, M; Walter, S
In recent years, natural fibres have been experimented to replace glass fibres in reinforcing thermosetting polymer. Since the interfacial adhesion between the raw natural fibres and the polymer matrix are often not adapted to the intended applications, the fibre surface most often requires a preliminary chemical modification. The fibres which were extracted from the Arundo donax L. Plant (called cane fibres), are little studied in the literature of fibre/polymer composites. In the present work, the cane fibres have been treated at constant soaking time with 2–8% NaOH aqueous solutions for 24 h. The composite reinforced by 6% NaOH-treated cane fibres, exhibited maximum improvements in tensile and flexural strength by 57% and 45% respectively. A combination of Fourier transform infrared, scanning electron microscopy, X-ray diffraction and moisture absorption techniques has been used for material characterisation. The crystallinity index yields information about fibre modification by NaOH. Such cane fibre composites could become an alternative to existing materials, with interesting tensile and flexural strengths, low cost and less ecological impact.